2014
DOI: 10.1186/1472-6882-14-351
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of Ceylon cinnamon extract on postprandial glycemia: alpha-amylase inhibition, starch tolerance test in rats, and randomized crossover clinical trial in healthy volunteers

Abstract: BackgroundPostprandial hyperglycemia is a known risk factor for the development of several health disorders including type 2 diabetes, obesity, oxidative stress, and cardiovascular diseases. One encouraging approach for a better control of postprandial glycemia is to reduce carbohydrate digestion. Cinnamon extracts have been known for managing blood glucose. However, their effects on inhibiting digestion of carbohydrate have been poorly analyzed to date. The aim of this study was to investigate the acute effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 33 publications
3
36
1
Order By: Relevance
“…The four groups were the diabetic control (DC) group, fed with HFD and 0.1% (grams per gram of body weight) water; the positive control (PC) group, fed with HFD and 30 mg kg −1 pioglitazone; the high‐dosage CoTEs (HCO) group, fed with HFD and 150 mg kg −1 CoTEs; and the low‐dosage CoTEs (LCO) group, fed with HFD and 30 mg kg −1 CoTEs. The dosages of HCO and LCO used herein were those reported in previous studies of C. zeylanicum bark extracts that could reduce postprandial hyperglycemia in rats . The dosage of pioglitazone used in rat models ranged from 10 to 30 mg kg −1 , and 30 mg kg −1 of pioglitazone was chosen to compare with the 30 mg kg −1 of CoTEs treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four groups were the diabetic control (DC) group, fed with HFD and 0.1% (grams per gram of body weight) water; the positive control (PC) group, fed with HFD and 30 mg kg −1 pioglitazone; the high‐dosage CoTEs (HCO) group, fed with HFD and 150 mg kg −1 CoTEs; and the low‐dosage CoTEs (LCO) group, fed with HFD and 30 mg kg −1 CoTEs. The dosages of HCO and LCO used herein were those reported in previous studies of C. zeylanicum bark extracts that could reduce postprandial hyperglycemia in rats . The dosage of pioglitazone used in rat models ranged from 10 to 30 mg kg −1 , and 30 mg kg −1 of pioglitazone was chosen to compare with the 30 mg kg −1 of CoTEs treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The dosages of HCO and LCO used herein were those reported in previous studies of C. zeylanicum bark extracts that could reduce postprandial hyperglycemia in rats. 19,20 The dosage of pioglitazone used in rat models ranged from 10 to 30 mg kg −1 , and 30 mg kg −1 of pioglitazone was chosen to compare with the 30 mg kg −1 of CoTEs treatment. The rats were treated for 12 weeks, and their glucose tolerance was measured by an OGTT every 4 weeks.…”
Section: Animals Diets and Treatmentsmentioning
confidence: 99%
“…Natural products can show an obvious role in the prevention of obesity and associated metabolic diseases. Cinnamon has been used as spice for a long time [18]. In addition it is gained from the inner bark of tropical evergreen cinnamon plants [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamon has been used as spice for a long time [18]. In addition it is gained from the inner bark of tropical evergreen cinnamon plants [18]. There are two main types of cinnamon: True or Ceylon cinnamon (Cinnamomum verum and C. zeylanicum) and cassia cinnamon ( C. aromaticum and C. burmannii ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular are directly related to lipoprotein metabolism and indirectly to the glycemic state (5). Natural products have good roles in the prevention of obesity and associated metabolic diseases (6). Previous research confirmed the efficacy of P. farcta beans powder as a beneficial agent to decrease LDL-C cholesterol and increase HDL-C cholesterol concentration, indicating a hypolipidemic property of P. farcta (7).…”
Section: Introductionmentioning
confidence: 97%